The managerial relevance of maintenance of work ability: A Finnish perspective - Tomi Hussi (The Research Institute of the Finnish Economy (ETLA), 2004)
Finland has pursued a law-based work ability policy for more than a decade. Many studies indicate that it has been very successful from a health point of view. It has also been demonstrated that it is economically feasible both on a micro and a macro level. In the present study, a number of experts in the field were interviewed about the content of the Finnish maintenance of work ability policy. The interview data was analysed from a managerial point of view. The analysis indicates that the Finnish maintenance of work ability policy works because it includes relevant management and leadership elements. It is not only a health programme, but is also based on measures that are conducive to economic growth.
Keywords: 330; Personalmanagement; Betriebliche Gesundheitspolitik; Arbeitsbedingungen; Theorie